STRUCTURING OF PEDAGOGICAL ABILITIES: ANALYSIS AND SYSTEMATIZATION OF DEFINING COMPONENTS (Physical Culture and Sport: Scientific Perspective, 2025)
The need for pedagogization in education is becoming more urgent every day, as knowledge is being productively accumulated by humanity, and the level of morality is falling, in particular because children and young people spend more and more time in impersonal institutions. Obviously, the results of the pedagogization of education are primarily in the introverted products of the work of pedagogical consciousness – new and improved pedagogical knowledge, skills, abilities, values, and motives. Analyzing these products, we come to the conclusion that among them, pedagogical abilities are largely ignored by the educational system. When we try to comprehend pedagogical abilities, we see that there are a lot of them, but all authors present them semi-chaotically, grouping them partially incorrectly, and most importantly, they are not memorable at all. This is unacceptable for a teacher who is trying to improve his or her level of pedagogical competence, because the first thing to do with a shortcoming in one's teaching is to find out what pedagogical ability is lacking, if any. Therefore, we tried to structure the existing pedagogical abilities in such a way that you would have to memorize a minimum and think logically to the maximum.The result of our structuring is the conclusion that all pedagogical abilities are either part of the 4 defining pedagogical abilities or the result of a combination of 2 or 4 of these pedagogical abilities, i.e., all pedagogical abilities can be logically derived from the 4 defining abilities. We describe the structure of pedagogical abilities as follows. 1) Intellectual: academic and research. 2. Sensitive: poetic, empathic, involvement, tact, emotional stability, facilitation. 3. Communicative: translational, reactive, coordinating. 4. Organizational (or managerial, or voluntary): limiting, distributing, focusing.Emotional (or expressive), suggestive, and major are a combination of sensitive and communication abilities. Pedagogical tact is a combination of sensitive and organizational abilities. The ability to see the dynamics of development and didactic abilities are a combination of intellectual and sensitive abilities. Pedagogical ingenuity is a combination of all 4 defining pedagogical abilities. Thus, it is possible to depict the structure of all pedagogical abilities as a graphical object, and the graphical way of presenting information is easy to remember.
Keywords: pedagogical abilities; defining pedagogical abilities; intellectual; sensitive; communication; organizational abilities; combination of defining pedagogical abilities